OCL Tools Report based on the IDE4OCL Feature Model - Chimiak-Opoka, Joanna; Demuth, Birgit; Awenius, Andreas; Chiorean, Dan; Gabel, Sebastien; Hamann, Lars; Willink, Edward (Electronic Communications of the EASST, 2011)
Previously we have developed the idea of an Integrated Development Environment for OCL (IDE4OCL). Based on the OCL community’s feedback we have also designed and published an IDE4OCL feature model. Here we present a report on selected OCL tools developed by the authors and their teams. Each author gives an overview of their OCL tool, provides a top level architecture, and gives an evaluation of the tool features in a web framework. The framework can also be used by other potential OCL users and tool developers. For users it may serve as an aid to choose a suitable tool for their OCL use scenarios. For tool developers it provides a comparative view for further development of the OCL tools. Our plans are to maintain the collected data and extend this web framework by further OCL tools. Additionally, we would like to encourage sharing of OCL development resources.